(untitled) (Canadian Hematology Today, 2022)
Multiple Myeloma (MM) is a malignancy of the plasma cells accumulating in the bone marrow. MM develops stepwise from the premalignant conditions, monoclonal gammopathy of undetermined significance (MGUS) and smoldering multiple myeloma (SMM). The Canadian Cancer Society estimates that in 2022 4,000 Canadians will be diagnosed, and 1,650 will die from MM. Survival rates have improved over the years with the development of novel treatment strategies, including proteasome inhibitors (PI), immunomodulatory drugs (IMiDs), targeted antibody and cellular therapies, and a selective inhibitor of nuclear export (SINE), as well as with the use of combinations of drugs. Although a number of patients will have a durable response following high-dose chemotherapy and autologous stem cell transplant (ASCT), MM remains an incurable malignancy with the majority of patients relapsing and eventually developing refractory disease (RRMM). Collaborative environments, in which pharmacists work with hematologists/oncologists, nurse practitioners, and supportive care teams, have been shown to improve adherence to the treatment plan. Prescription of appropriate prophylaxis in combination with various treatment strategies may reduce the number and duration of treatment delays. Intensified clinical and pharmaceutical care, including medication management and structured patient counseling for patients on oral anticancer drugs, has been shown to reduce the number of medication errors and severe side effects while improving the patient’s treatment experience. Nurses play a vital role in the management of toxicities as they educate, support, and advocate for patients. This report discusses the management of adverse events (AEs) related to both established agents and novel therapies for the optimal management of patients with RRMM. Established and novel therapies are often used in combination, which presents the potential for overlapping toxicities. The optimal combination therapies including the sequencing of various regimens are yet to be determined. Basic research and clinical trials with investigational agents are ongoing in an effort to improve both the depth and duration of response in newly diagnosed patients and those with RRMM with the aim of finding the best treatment options for every patient.